Teaching of the integrated topics on drug abuse as a strategy to eradicate drug abuse among secondary school students in Machakos District, Kenya - (:unkn) unknown (My University, 2012)
The problem of drug abuse has been an area of concern in Kenya for the last two decades. The previous studies carried out in this area revealed that drug abuse has been on the increase at the secondary school level in Kenya. The purpose of this study was to investigate teaching of the integrated topics on drug abuse in the secondary school curriculum as a strategy to wipe out the problem of drug abuse among students in Machakos District. The specific objectives of the study were to: establish the prevalence of drug abuse at the secondary school level according to gender, locality, boarding or day and religious practices, examine which topics on drug abuse are integrated in the secondary school curriculum, identify the methods teachers employ to teach the integrated topics on drug abuse in the secondary school curriculum, establish the teaching and learning materials that are used to teach the integrated topics on drug abuse in the secondary school curriculum and establish the factors that hinder the teaching of the integrated topics on drug abuse in the secondary school curriculum. The results of this study would add more information to the present literature on teaching of the integrated topics on drug abuse in the secondary school curriculum. A survey study was carried out in Machakos District. The target population of this study comprised of 19187 students, 3739 teachers and 62 principals. A sample of 774 respondents was drawn from 24 randomly selected secondary schools through stratified and simple random sampling techniques.·It comprised of 24 principals, 280 teachers and 470 students. The study utilized four research instruments: three questionnaires and interview schedule. The validity and reliability of the instruments was established by piloting the instruments in two pilot schools in Machakos District. The reliability of the research instruments was determined through the split-half method. The reliability index for the research instrument was: Students' Drug Abuse Education Questionnaire (0.86), Teachers' Drug Abuse Education Questionnaire (0.84) and Principals' Drug Abuse Education Questionnaire (0.85). The data collected was analyzed using frequencies, percentages, mean and median. The qualitative data was analyzed through description of the interviewees' opinions. The main findings of the study were: the prevalence of drug abuse according to gender was: Boys' (11.19%), Girls' (9.58%) and mixed sex (9.49%) schools. The urban schools had a prevalence of 10.73% whereas it was 9.66% in the rural ones. The topics on drug abuse were integrated in the secondary school curriculum, teachers used a variety of methods to teach integrated topics on drug abuse, teachers utilized several teaching materials to teach the integrated topics on drug abuse, the teaching of the integrated topics on drug abuse was hindered by limited teaching resources. The teaching of the integrated topics on drug abuse had reduced the drug menace. The following recommendations were made in order to improve teaching of the integrated topics on drug abuse: teachers should adopt the learner- centered methods in teaching the integrated topics on drug abuse and schools should be adequately equipped with teaching resources required to teach the integrated topics on drug abuse.